2007
DOI: 10.1111/j.1574-6968.2007.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of compound 48/80-sensitized Pseudomonas aeruginosa to the hydrophobic biocide triclosan

Abstract: Pseudomonas aeruginosa is intrinsically resistant to the hydrophobic biocide triclosan, and yet it can be sensitized to low concentrations by permeabilization of the outer membrane using compound 48/80. A selective plating assay revealed that compound 48/80-permeabilized YM64, a triclosan-recognizing efflux pump-deficient variant, was unable to initiate growth on a medium containing triclosan. Macrobroth dilution assay data revealed that treatment with compound 48/80 synergistically decreased minimal inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It has been reported that inactivation of the MexAB-OprM multidrug efflux pump results in a decrease of P. aeruginosa PAO1 triclosan resistance from 1,000 g/ml to 16 g/ml (4, 5). However, other investigators have reported that inactivation of the MexABOprM efflux pump had either no effect (4, 10) or a minimal effect (10) on triclosan resistance unless the outer membrane was permeabilized by chemical agents (10). The differences among the MexAB-OprM reports may be due to the fact that the workers who reported the dramatic effects of MexAB-OprM inactivation (5) solubilized triclosan with 2-methoxyethanol, and this solvent may have permeabilized the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inactivation of the MexAB-OprM multidrug efflux pump results in a decrease of P. aeruginosa PAO1 triclosan resistance from 1,000 g/ml to 16 g/ml (4, 5). However, other investigators have reported that inactivation of the MexABOprM efflux pump had either no effect (4, 10) or a minimal effect (10) on triclosan resistance unless the outer membrane was permeabilized by chemical agents (10). The differences among the MexAB-OprM reports may be due to the fact that the workers who reported the dramatic effects of MexAB-OprM inactivation (5) solubilized triclosan with 2-methoxyethanol, and this solvent may have permeabilized the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The supply sources were as follows: malonyl coenzyme A (malonyl-CoA), acetyl-CoA, fatty acids, triclosan, NADH, NADPH, and antibiotics were from Sigma; Takara Biotechnology Co. provided molecular biology reagents; Novagen provided pET vectors; American Radiolabeled Chemicals, Inc., provided sodium [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate (specific activity, 50 mCi/mM); Invitrogen provided the Ni 2 -agarose column; and Bio-Rad provided the UNOsphere Q strong anion-exchange media and the Quick Start Bradford dye reagent. All other reagents were of the highest available quality.…”
Section: Methodsmentioning
confidence: 99%
“…[271] As predicted from the synergy between the pumps and the OM barrier, an OM-permeabilizing polycationic compound 48/80[272] increased the susceptibility of P. aeruginosa to the hydrophobic biocide triclosan. [273]…”
Section: Drug Efflux In Gram-negative Bacteriamentioning
confidence: 99%
“…The most frequently described Gram-negative mechanisms for defense against TCS are active efflux via pumps belonging to the resistance-nodulation-cell division (RND) family (13,43) and, to some extent, exclusion by making the cell envelope impermeable (11,18). Accordingly, the majority of the induced genes in R. rubrum were related to efflux systems.…”
Section: Discussionmentioning
confidence: 99%